A REVIEW STUDY ON LEGAL REGULATION OF AGRICULTURAL LABOUR IN INDIA - Dr. K. Ravindra (Galaxy International Interdisciplinary Research Journal, 2021)
The Indian Planners have committed themselves to improve the conditions of Agricultural Labour. the Government of India gave special consideration to the landless agricultural labour, this is one section which has really a very hard time and which deserves very special consideration. Still seasonal unemployment is a characteristic feature of Agricultural sector and under employment of man power is inherent in the system of family farming. Unlike industrial labour, agricultural labour is difficult to define. The reason is that unless capitalism develops fully in agriculture, a separate class of workers depending wholly on wages does not come up. In this paper studied about agricultural Labor Laws and their Review.